KESADARAN LINGKUNGAN IBU RUMAH TANGGA DALAM PENGELOLAAN SAMPAH RUMAH TANGGA - Ibnu Mustopo Jati; Desy Safitri; Sujarwo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The aim of this research is to describe the environmental awareness of housewives in household waste management and efforts to cultivate environmental awareness among housewives in household waste management. The research was conducted at Bank Sampah Hijau Selaras Mandiri located at Jl. Kompleks Angkasa Pura Blok PQRS RT.14/RW.06, Kelurahan Kebon Kosong, Kecamatan Kemayoran, Kota Jakarta Pusat. This study utilized a descriptive method with data collection techniques such as questionnaires, observations, interviews, and documentary studies. Descriptive data analysis was employed as the data analysis technique in this study. Purposive sampling was used, with the participants being waste bank members acting as housewives. The research findings indicate that 53% of housewives have a moderate level of environmental awareness in managing household waste, while 47% have a high level of environmental awareness. The housewives have a general belief in recognizing the urgency of environmental issues, possess information and knowledge about household waste and its management, demonstrate individual attitudes in perceiving and treating waste and their environment, and exhibit pro-environmental behaviors through eco-friendly lifestyle changes. The research also shows that housewives have implemented waste management in accordance with the Regional Regulation of the Special Capital City of Jakarta Number 3 of 2013 concerning Waste Management. The efforts undertaken by Bank Sampah Hijau Selaras Mandiri in fostering environmental awareness among housewives in household waste management include: 1) implementing programs to their fullest extent, 2) providing socialization and counseling, 3) disseminating information, 4) delivering education, and 5) gives rewards and punishments.